Structure and thermal stability of sodium and carbonate-co-substituted strontium hydroxyfluorapatites. (20th April 2018) - Hidouri, Mustapha; Dorozhkin, Sergey V.
Abstract : Physicochemical characterization of sodium and carbonate co-substituted strontium hydroxyfluorapatite resulting in pure apatite with ionic vacancies as a biomaterial. Abstract : The present study was aimed at investigating the co-substitution of sodium and carbonate in strontium hydroxyfluorapatites because these compounds have many similarities to the mineral phase of bones. Herein, three series of sodium- and carbonate-doped strontium hydroxyfluorapatites were prepared via a co-precipitation method. Chemical analysis via inductively coupled plasma-atomic emission spectrometry (ICP-AES), X-ray diffraction (XRD), Rietveld refinement, Fourier transform infrared spectroscopy (FTIR), 31 P nuclear magnetic resonance (NMR), and differential and gravimetric thermal analysis (DTA–GTA) characterizations were employed for the identification of the obtained products. Sodium- and fluoride-doped strontium hydroxyapatite was found to be a pure apatitic phase containing ionic vacancies. Rietveld analysis showed a significant decrease in the a lattice parameter as sodium and fluoride levels increased, whereas in carbonate- and fluoride-doped strontium hydroxyapatite, both the a and the c lattice parameters decreased as the amounts of carbonate that were added increased. The obtained powders were a B-type carbonate apatite with vacancies. The co-substitution of sodium and carbonate in the hydroxyfluorapatite structure typically gave rise to B-type carbonate apatite with vacancies. Thermal investigation in the range of 500–1200 °C revealed that decomposition occurred at a temperature of about 800 °C, and Sr3 (PO4 )2 was formed.